2004 International Conference on Power System Technology, 2004. PowerCon 2004.
DOI: 10.1109/icpst.2004.1460015
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic minimization in the operation of static VAR compensators for unbalanced reactive power compensation

Abstract: Absfruct-Phase-wise unbalanced reactive power compensations are required in distribution systems for dynamic power factor correction and terminal voltage stabilization. Shunt compensators are generally used to reduce or cancel the phasewise unbalanced reactive power (VAR) demand and to minimize the reactive power drawn from the AC supply lines. Static VAR compensators are preferred over traditional VAR compensators for this purpose. The operation of thyristor-controlled compensators at various conduction angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Thukaram et al in [8] have analyzed a fixed capacitorthyristor-controlled reactor (FC-TCR) type of compensator for minimum harmonic injections in terms of . The authors have concluded that the compensator operation beyond a certain range of triggering delay angles may increase the harmonic components and, thus, the compensator capacitor and reactor size should be selected based on the overall requirement of meeting the loads.…”
Section: Comparison With Current Technologymentioning
confidence: 99%
“…Thukaram et al in [8] have analyzed a fixed capacitorthyristor-controlled reactor (FC-TCR) type of compensator for minimum harmonic injections in terms of . The authors have concluded that the compensator operation beyond a certain range of triggering delay angles may increase the harmonic components and, thus, the compensator capacitor and reactor size should be selected based on the overall requirement of meeting the loads.…”
Section: Comparison With Current Technologymentioning
confidence: 99%
“…Since the fundamental currents are in the same phase for both bank line currents, the maximum value of total TCR fundamental current (for triggering angle 90°) is given below: (17) Since the relative values of L 1 and L 2 are fixed in (13), combining (15) and (16), the maximum value of total TCR fundamental current (for triggering angle 90°) is given below:…”
Section: Bankmentioning
confidence: 99%
“…On the other hand when Q comp is negative, and its magnitude is more than rated value then the controller sets α corresponding to maximum TCR reactive power Q max . Otherwise, the calculated Q comp is directly used for α generation following (39) and (40), described in Section 7.…”
Section: Computation Of Firing Angle αmentioning
confidence: 99%
“…However, these schemes need additional investment [37] and space to accommodate filtering stages. Thus, improvement of switching schemes of SVC is also studied to minimise harmonics generated by TCR without using additional filter [38][39][40][41]. However, these switching schemes are insufficient to a wider range of TCR harmonics as well as harmonics generated by non-linear load.…”
Section: Introductionmentioning
confidence: 99%